Perspectives of Sustainable Development for the Italian University Museums - Corradini, Elena (Actual Problems of Theory and History of Art, 2022)
The Italian university museums are characterized by the multiple disciplines they represent, both scientific and artistic. The article presents some future perspectives of sustainable development that can be obtained as the result of their activities in the network and attempts to overcome the difficulties of their organizations with different management systems, in many cases still connected to the departments of reference. The starting point is the first census made by the Rectors of Italian Universities Conference (CRUI). From this census, a detailed review of the museum heritage of 39 Italian Universities and its organization is emerged. It can make possible the creation of a National Observatory which is essential first of all to offer advice for the accreditation procedures provided by the National Museum System. Through this accreditation, the university museums will be able to join the network of the Italian museums and cultural places (state, public, and private) for a unified vision of the development of Italian museums regardless of their ownership, size, type, and form of management to create a governance of heritage based on sustainability, innovation, participation, and accessibility. The accreditation will allow to strengthen their mutual knowledge and a useful exchange of good practices for a common development and to verify their organization, the management of their juridical and economic profiles, of their collections and their relationships with their regions. Since the university museums lacked an updated space to rapidly disseminate the free expressions of their ideas and projects, an online bilingual monthly magazine was created.